STYLISTIC TREND IN LINGUOCULTUROLOGY (Conference Zone, 2022)
Present-day stylistics is greatly influenced by Cultural Linguistics, and it is accounted for by the fact that there are close relationships between these sciences. Stylistics, as is known, has always been a “human-oriented” discipline, therefore, the development of Cultural Linguistics, provides fresh impetus for stylistics which embarks on a new stage of its development within the framework of Cognitive Linguistics and Linguocultural Stylistics.